The effect of Zinc chelate and Potassium sulfate topdressing on alleviating the Cadmium (Cd) and Nitrate (NO3-) toxicity in potato tubers of Ardabil province, Iran - Seyyede Khamsa Asbaghian Namini; Mohammad Jafar Malakouti; Akbar Ghavidel (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Contamination of tuberous vegetables such as potato (Solanum tuberosum L.) with Cadmium (Cd) and Nitrate (NO3-) due to the imbalanced fertilization may pose health risks to consumers. Potato is one of the dominant agricultural vegetables in Iran which is consumed in different ways. Excessive amounts of Cd and NO3- in potatoes can lead to organ dysfunction and various diseases. The aim of this study was to investigate the role of Zn-fertilizers on increasing yield and reducing the Cd concentration and also monitoring the NO3- content in potato tubers of Ardabil province. For this purpose, In the first phase, potato tubers were sampled from 10 most important markets in the form of imbalanced completely randomized design in 2019 and the concentration of Cd when consumed with and without potato peel was assessed, then, in the second phase, the effect of Zn-fertilizers on the yield and concentration of Cd in high-risk areas was investigated in 2020 growing season. The results indicated that the maximum concentration of Cd among the samples was 0.14 mg kg-1 fresh weight and the minimum was 0.02 mg kg-1 fresh weight. According to the results, there was no significant difference between potato samples analyzed with peel and without peel. Therefore, in the second phase, in order to investigate the effect of Zn-fertilizers topdressing on potato tubers yield and Cd concentration, an experiment was conducted in randomized complete block design with 3 treatments and 3 replications in Ardabil University's farm. Experimental treatments were the T1 (control) = Farmer's conventional fertilization with no Zn-fertilizer; T2 = T1 + 2 kg ha-1 Zn-chelate; T3 = T2 + applying 50 kg ha-1 soluble sulfate potassium containing Zn-chelate. The results illustrated that in control plots, while the yield was 23.3 tons per ha and the percentage of dry matter was 19.0 percent, the significant increase (p<0.01) up to 34.0 tons per ha with 24 percent of dry matter was obtained in SSOP+Zn chelate treatment. Also there was a significant difference (p<0.01) between Cd concentration in control treatment and treatments in which Zn-fertilizers have been used. The maximum Cd concentration has observed in control treatment with 0.13 mg kg-1 fresh weight and the minimum has obtained from SSOP+Zn chelate treatment by 0.01 mg kg-1 fresh weight. About Nitrate concentration in potato tubers of the field area, all data were located below the threshold concentration (60 mg kg-1 fresh weight). Therefore, for obtaining healthy agricultural products, using Zn-fertilizers in the agricultural soils with Zn deficiency should be considered seriously. By practicing balanced fertilization, i.e. applying Zn-fertilizers especially by topdressing method, the quality and quantity of agricultural products as potato will be upgraded and the Cd and NO3- concentration will be decreased significantly, the country's quality of nutrition will improve and hence, the problem of malnutrition will be solved.